Unique system of photoreceptors in sea urchin tube feet - Ullrich-Lüter, Esther M (National Academy of Sciences, 2011)
Different sea urchin species show a vast variety of responses to variations in light intensity; however, despite this behavioral evidence for photosensitivity, light sensing in these animals has remained an enigma. Genome information of the recently sequenced purple sea urchin (Strongylocentrotus purpuratus) allowed us to address this question from a previously unexplored molecular perspective by localizing expression of the rhabdomeric opsin Sp-opsin4 and Sp-pax6, two genes essential for photoreceptor function and development, respectively. Using a specifically designed antibody against Sp-Opsin4 and in situ hybridization for both genes, we detected expression in two distinct groups of photoreceptor cells (PRCs) located in the animal's numerous tube feet. Specific reactivity of the Sp-Opsin4 antibody with sea star optic cushions, which regulate phototaxis, suggests a similar visual function in sea urchins. Ultrastructural characterization of the sea urchin PRCs revealed them to be of a microvillar receptor type. Our data suggest that echinoderms, in contrast to chordates, deploy a microvillar, r-opsin–expressing PRC type for vision, a feature that has been so far documented only in protostome animals. Surprisingly, sea urchin PRCs lack any associated screening pigment. Indeed, one of the tube foot PRC clusters may account for directional vision by being shaded through the opaque calcite skeleton. The PRC axons connect to the animal internal nervous system, suggesting an integrative function beyond local short circuits. Because juveniles display no phototaxis until skeleton completion, we suggest a model in which the entire sea urchin, deploying its skeleton as PRC screening device, functions as a huge compound eye.